DETECTION OF DIFFUSION OF RESOURCE CIRCULARITY AND PRINCIPLES OF FORMATION OF SOCIO-ECONOMIC BENEFITS IN AGRIBUSINESS - KHODAKYVSKYY, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The identification of the diffusion of resource circularity of agribusiness by components of influence is substantiated. The feasibility of the system of diffusion of resource circularity of agribusiness is proposed and proven. The systemic connections of the external environment of agribusiness are investigated and established by the elements of the formation of benefits, alternatives and efficiency. The degree of diffusion of resource provision of the sphere of agricultural products processing is argued. The globality of the functional system of diffusion of resource circularity of agribusiness in the ecosystem environment is investigated from the position of the receipt of production resources for the spheres of agriculture. The systemic connections of the formation of benefits, alternatives and efficiency of resource circularity of agribusiness outside the scope of economic relations are investigated. The formation of benefits and alternatives of resource circularity of agribusiness is schematized from the position of the influences of the natural and anthropogenic environment, which are integral and especially important elements of its resource functioning. The geographical, biogenic and abiotic components are highlighted and substantiated in the system of influences by the elements of the formation of benefits, alternatives and efficiency of diffusion of resource circularity of agribusiness. The feasibility of a systematic study of the formation of benefits, alternatives and the effectiveness of the diffusion of resource circularity of agribusiness from the position of the formation of production relations in the external environment of agricultural production within the existing ecosystem is indicated. The organizational consciousness of the processes of circularity of resource provision of agribusiness is substantiated in identifying the need for the processes of production, social and environmental integration. The need to form the processes of resource circularity of agribusiness at the initial stages of consumption of material and resource and energy supply is proven, which forms the mission of circular development of the ecosystem environment as the impossibility of environmental pollution processes.
Keywords: diffusion; agribusiness; resource circularity; alternatives; efficiency; benefits; socio-economic environment; systematization; external environment